2018
DOI: 10.1002/ejoc.201801490
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Peptide–Adenine Conjugates as a New Tool for Monitoring Protease Activity

Abstract: We took advantage of the powerful adenine SERS (Surface Enhanced Raman Spectroscopy) probe to design peptide–adenine conjugates as candidates for use as serine protease substrates. Whereas the direct introduction of the peptide sequence on the adenine exocyclic N6 amine gave an imidazopurinone derivative, the introduction of an aminoethyl linker between the adenine group and the peptide chain led to the expected candidate probes. These potential substrates were then evaluated for monitoring the hydrolytic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Controlled isomerization of exocyclic groups anchored at the N 6 position have not previously been reported in a biological system, though rearrangements of exocyclic groups at N 6 have been induced chemically in abiotic systems. Under harsh conditions, Ross H. Hall and Girish B. Chheda reported carboxymethyl products resulting from tricyclization, hydrolysis, and deamination of adenine aminoacylated at N 6 ( 27, 28 ). A more recent study aiming to synthesize peptides conjugated to adenine at N 6 similarly reported a mixture of products upon deprotection of the primary amine in strong organic acid ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled isomerization of exocyclic groups anchored at the N 6 position have not previously been reported in a biological system, though rearrangements of exocyclic groups at N 6 have been induced chemically in abiotic systems. Under harsh conditions, Ross H. Hall and Girish B. Chheda reported carboxymethyl products resulting from tricyclization, hydrolysis, and deamination of adenine aminoacylated at N 6 ( 27, 28 ). A more recent study aiming to synthesize peptides conjugated to adenine at N 6 similarly reported a mixture of products upon deprotection of the primary amine in strong organic acid ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Under harsh conditions, Ross H. Hall and Girish B. Chheda reported carboxymethyl products resulting from tricyclization, hydrolysis, and deamination of adenine aminoacylated at N 6 ( 27, 28 ). A more recent study aiming to synthesize peptides conjugated to adenine at N 6 similarly reported a mixture of products upon deprotection of the primary amine in strong organic acid ( 28 ). Distinct from these synthetic approaches, enzymatic momylation leads to formation of a single, detectable hypermodification via isomerization of the exocyclic glycyl group, suggesting that the Mom enzyme favors 6- N cmdA over any other chemically possible product.…”
Section: Resultsmentioning
confidence: 99%
“…While the field of KLK’s inhibitor discovery is relatively underdeveloped despite very huge interest in several therapeutic areas, recent reviews highlight the interest and need for further works. …”
Section: Resultsmentioning
confidence: 99%
“…While the field of KLK's inhibitor discovery is relatively underdeveloped despite very huge interest in several therapeutic areas, recent reviews highlight the interest and need for further works. [24][25][26][27][28] developed a yeast-displayed mutant library of the human amyloid precursor protein Kunitz protease inhibitor domain (APPI) to derive serine protease inhibitors especially of KLK6. 29 Recently, Miller and co-workers have reported depsipeptides as potent KLK6's inhibitors to derive activity-based probes (Compound II, Chart 1).…”
Section: Rational Design Of Para-benzylamine Derivativesmentioning
confidence: 99%